2022
DOI: 10.1016/s1470-2045(21)00581-7
|View full text |Cite
|
Sign up to set email alerts
|

The global burden of adolescent and young adult cancer in 2019: a systematic analysis for the Global Burden of Disease Study 2019

Elysia M Alvarez,
Lisa M Force,
Rixing Xu
et al.

Abstract: Background In estimating the global burden of cancer, adolescents and young adults with cancer are often overlooked, despite being a distinct subgroup with unique epidemiology, clinical care needs, and societal impact. Comprehensive estimates of the global cancer burden in adolescents and young adults (aged 15-39 years) are lacking. To address this gap, we analysed results from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2019, with a focus on the outcome of disability-adjusted life-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(78 citation statements)
references
References 34 publications
4
62
0
1
Order By: Relevance
“…Evidence from studies in other countries has also con rmed the existence of socio-economic inequalities (SDI) in the distribution of cancer burden. For example, in con rmation of our ndings, the highest age-standardized incidence rates occurred in high SDI and high-middle SDI countries [27]. O'Connor et al…”
Section: Discussionsupporting
confidence: 80%
“…Evidence from studies in other countries has also con rmed the existence of socio-economic inequalities (SDI) in the distribution of cancer burden. For example, in con rmation of our ndings, the highest age-standardized incidence rates occurred in high SDI and high-middle SDI countries [27]. O'Connor et al…”
Section: Discussionsupporting
confidence: 80%
“…To better exhibit the age distribution of IE burden, IE patients were classified into 5 groups, namely those aged under 5 years, from 5 to 14 years, from 15 to 49 years and from 50 to 69 years, as well as above 70 years. Social developmental index (SDI) was a composite indicator of total fertility, per capita income, and the years of schooling, which was formulated to reflect the social developmental degree (17). The value ranged from 0 to 1, where 0 represented the fewest years of schooling, lowest per capita income, and highest fertility, whereas 1 represented the opposite.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…A recent study by the GBD 2019 Adolescent Young Adult (AYA) Cancer Collaborators 1 reported that countries outside the highest sociodemographic quintile, including those in South America, southern sub-Saharan Africa, and Asia, carried the heaviest burden of cancer among AYA (defined as age 15-39 years). We would like to draw attention to Southeast Asia (SEA), a region comprising 11 countries and over 650,000,000 people, of whom over 260,000,000 are AYA.…”
Section: Adolescents and Young Adults With Cancer: Considerations Fro...mentioning
confidence: 99%
“…Furthermore, several SEA countries, including the populous countries of the Philippines, Indonesia, and Thailand, have a relatively high AYA cancer burden, and fall within the second highest quintile in terms of age-standardized disabilityadjusted life-years attributable to AYA cancers. 1 The socioeconomic sequelae of cancer are relevant to AYA in the region, as despite socioeconomic diversity in SEA, the majority of the population resides in lower middle income countries (LMICs). The ACTION study, a longitudinal survey of the socioeconomic burden and survivorship following cancer surgery conducted in eight LMICs within SEA, found that almost one in three patients experienced financial catastrophe within 3 months, with women and individuals of lower socioeconomic status disproportionately affected.…”
Section: Adolescents and Young Adults With Cancer: Considerations Fro...mentioning
confidence: 99%